1997
DOI: 10.1007/s00585-997-1429-8
|View full text |Cite
|
Sign up to set email alerts
|

Day-to-day thermosphere parameter variation as deduced from Millstone Hill incoherent scatter radar observations during March 16-22, 1990 magnetic storm period

Abstract: Abstract. A self-consistent method for day-time F2-region modelling was applied to the analysis of Millstone Hill incoherent scatter observations during the storm period of March 16-22, 1990. The method allows us to calculate in a self-consistent way neutral composition, temperature and meridional wind as well as the ionized species height distribution. Theoretically calculated x e (h) pro®les ®t the observed daytime ones with great accuracy in the whole range of heights above 150 km for both quiet and disturb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Auroral and subauroral heating and transport processes lead also to disturbed regions of neutral gas distributions. For the present interval this was investigated by Mikhailov and FoÈ rster (1997). The disturbance region is characterised by enhanced densities of neutral molecular species with a relatively sharp boundary toward mid-latitudes.…”
Section: Energetic Particle Precipitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Auroral and subauroral heating and transport processes lead also to disturbed regions of neutral gas distributions. For the present interval this was investigated by Mikhailov and FoÈ rster (1997). The disturbance region is characterised by enhanced densities of neutral molecular species with a relatively sharp boundary toward mid-latitudes.…”
Section: Energetic Particle Precipitationsmentioning
confidence: 99%
“…During the period of our study, this boundary was probably just northward of Millstone Hill as indicated by the steplike decrease in x e at about 55 geomagnetic latitude and moved over the radar station in the course of the night. From model studies with an iterative optimisation code the daytime values of the neutral gas parameters were estimated using measured Millstone Hill radar pro®les by Mikhailov and FoÈ rster (1997). A numerical model study of the storm period should take into account the speci®ed neutral gas distributions.…”
Section: Energetic Particle Precipitationsmentioning
confidence: 99%
“…In one of them used in present study, exospheric temperature T ex is included to the list of unknown parameters. This way of searching for T ex is different from the earlier approach used in Mikhailov and Schlegel (1997), Mikhailov and Foster (1997), Mikhailov and Förster, (1997), and it turned out to be more straightforward and efficient, as well as more general, as it uses the most reliable parameter, N e (h) observed with the IS method, while T e (h) and T i (h) profiles depend on the ion composition model applied during the incoherent scatter data analysis (e.g. Lathuillère et al, 1983;Alcaydé et al, 1996).…”
Section: Model Calculationsmentioning
confidence: 99%
“…Therefore, a model which takes into account the photo-ionization of neutral atmospheric species by solar EUV, a set of main chemical processes, vertical plasma transport due to diffusion, thermospheric winds and electric fields may be used for such an analysis. The model used earlier for EISCAT and Millstone Hill incoherent scatter (IS) data analysis (Mikhailov and Foster, 1997;Mikhailov and Förster, 1997;Schlegel, 1997, 1998) Nusinov (1992) is used to calculate the photo-ionization rates in 35-wavelength intervals (100-1050Å). The photo-ionization and photo-absorption crosssections are obtained from Torr et al (1979) and Richards and Torr (1988).…”
Section: Model Calculationsmentioning
confidence: 99%
“…On the other hand the temperature dependence given by McFarland et al (1973) is very steep. It was e ciently used in our calculations to mimic the increase of this reaction rate due to vibrationally excited N 2 at high solar activity (Mikhailov and FoÈ rster, 1997;Mikhailov and Foster, 1997;Mikhailov and Schlegel, 1998). Recent owing afterglow measurements by Hierl et al (1997) carried out at T n T i T v 300±1600 K con®rmed the results by Schmeltekopf et al (1968) and showed that the translation energy dependencies for the vibrationally excited species are the same as those for the species being at the ground level (v 0).…”
Section: Introductionmentioning
confidence: 67%